Performance measurements on NIF beamlines for future experiments to support polar direct drive. (May 2016) - Crane, J K; Kruschwitz, B; Yang, S T; Bowers, M; Browning, D; Budge, T; Canning, D; Chou, J; Consentino, A; Nicola, J M Di; Dixit, S; Dorrer, C; et al.
Abstract: We are studying the implementation of polar direct drive (PDD) ignition experiments on the National Ignition Facility (NIF) laser system. Part of this preparation involves testing the performance of the NIF laser system over a broader span of center wavelengths, 3.6 nm, where the laser currently operates and that gain models describe. The temporal shape for the PDD pulses consists of a drive pulse preceded by three lower power "picket pulses". These picket pulses require a multi-FM sinusoidal phase modulation format with a bandwidth of ∼ 200 GHz and a more dispersive grating in the preamplifier module (PAM) for smoothing-by-spectral-dispersion (SSD). In this paper we discuss recent measurements of gain on the NIF laser system over this broader wavelength range. We measured FM-to-AM conversion over the 3.6 nm wavelength range. The possibility of pinhole closure due to the larger bandwidth and dispersion associated with multi-FM SSD was studied at LLE on the OMEGA EP laser.